El gobierno de las megalópolis, el caso de Brasil, São Paulo: gestión metropolitana, descentralización y participación como desafíos simultáneos - Pires, Valdemir [UNESP]; Gaeta, Antonio Carlos [UNESP] (My University, 2010)
The government of a megalopolis, such as São Paulo, shows singular challenges that do not exist in less complex urban contexts. Being a city of a country with a recent industrialized economy, with an income (functional and geographical) highly concentrated, that has resumed the democracy for only one quarter of a century, this megacity lives with its own political and organizational assignments, due to the contradictory character of the political behavior of its habitants/ voters and of the traditionalist nature of populism and patronage in the relationship between the rulers and the ruled and between the Executive and Legislative powers at the local level. In such context, the difficulties to prosecute the assignments of the metropolitan organization, the decentralization and the institutionalization of citizen participatory channels in the governance and administrative activities are huge. The centrifuge forces (of the decentralization of the local government, through subprefectures), the centripetal forces ( of the metropolitan organization process) and the diffuse forces (of the claiming popular participation) act simultaneously over the deciding processes, in São Paulo, receiving, still, state and national political influences, since the city is a very significant historically producer of political and electoral capital. The analysis of the recent experience of the creation of the subprefectures and the representative counsels (fixed in the Municipality Organic Law of 1990) and the attempt to implement the participatory budgeting, in two occasions (1989-1992 and 2001-2004), reveal some of the social and political reasons that make difficult the establishment of a solidly democratic governance and of a more efficient public administration in the metropolitan area of São Paulo.

El gobierno de una megalópolis como São Paulo presenta desafíos singulares, que son inexistentes en contextos urbanos menos complejos. Tratándose de una ciudad de un país de economía recientemente industrializada, con renta (funcional y geográfica) altamente concentrada, y que retomó la democracia hace apenas un cuarto de siglo, esta mega-ciudad convive, adicionalmente, con tareas políticas y organizativas propias, derivadas del carácter contradictorio del comportamiento político de sus habitantes/electores y de la naturaleza tradicionalmente populista y clientelista de la relación entre gobernantes y gobernados y entre los poderes Ejecutivo y Legislativo a nivel local. En este contexto son enormes las dificultades para llevar a cabo las tareas de organización metropolitana, de descentralización y de institucionalización de canales de participación ciudadana en las actividades gubernamentales y administrativas. Las fuerzas centrífugas (de descentralización del gobierno municipal, por medio de subprefecturas), las fuerzas centrípetas (del proceso de organización metropolitana) y las fuerzas difusas (de la participación popular reivindicativa) actúan simultáneamente sobre los procesos decisorios en São Paulo, y están influidos además por la política estatal y nacional, ya que la ciudad es un polo generador de capital político-electoral muy significativo históricamente. El análisis de la experiencia reciente de creación de subprefecturas y consejos de representantes (previstos en la Ley Orgánica del Municipio de 1990) y el intento de implementación del presupuesto participativo en dos ocasiones (1989-1992 y 2001-2004) revelan algunos de los condicionantes sociales y políticos que dificultan el establecimiento de un gobierno sólidamente democrático y de una gestión pública más eficiente en la región metropolitana de São Paulo.
The governments of the megalopolises, the case of Brazil - São Paulo: metropolitan administration, decentralization and participation as simultaneous challenges
Keywords: Megalopolis; decentralization; metropolitan cities; citizen participation; São Paulo; governance; Megalópolis; metropolización; descentralización; participación ciudadana; São Paulo; gobierno; metropolização; Região Metropolitana de São Paulo; gestão das regiões metropolitanas; planejamento regional